The Acute Management of Sport Concussion in Pediatric Athletes. (October 2015) - Resch, Jacob E.; Kutcher, Jeffrey S.
During the past two decades the focus on sport concussion has increased significantly. Young athletes represent the most vulnerable population to sustain a sport concussion yet receive the least amount of attention. Specifically, young athletes who sustain a sport concussion can go unrecognized and continue to participate in sport putting them at an increased risk for a more significant injury. The purpose of this review is to provide a clinical framework for the evaluation and management of sport concussion. In addition, this review provides considerations for health care professionals in regard to clinical measures and follow-up strategies during the acute phase following concussion in young concussed athletes following injury.